CALLUS FORMATION FROM ISOLATED MICROSPORE CULTURE IN RADISH (RAPHANUS SATIVUS L.) - B. Tuncer (Journal of Animal and Plant Sciences, 2017)
In this study, the effects of applications of colchicine on microspore cultures were evaluated in 4 radish (Raphanussativus L.) varieties. For this purpose, 5 different concentrations of colchicine (0, 10, 25, 50, and 75 mg L-1) were applied under dark conditions at 4°C to microspores that had been isolated in Gamborg’s medium containing 13% (w/v)sucrose (B5-13). After the application of colchicine the microspores were kept for 1 day at 32.5°C in1/2 x Nitsch and Nitschliquid media supplemented with13% (w/v)sucrose (1/2 NLN-13) at a density of 40.000 microspore mL-1and transferred for culturing under dark conditions at 25°C. Colonies of callus were observed in Petri dishes 4–5 weeks after the microspore isolation. In this study, the 50 mg L-1 dose of colchicine was found to be more effective in terms of callus formation. The highest callus formation was achieved from the large round radish (cv. Burkır) (6.63 calli/Petri dish)and the standard small rooted radish (cv. Cherry Belle)(5.73 calli/Petri dish) varieties.
Keywords: Microspore culture; callus; colchicine; Raphanussativus L